Long-term prognostic value of computed tomography-based attenuation correction on thallium-201 myocardial perfusion imaging: A cohort study - Jei-Yie Huang (Public Library of Science (PLoS), 2021)
Background Myocardial perfusion imaging (MPI) is a well-established diagnostic tool to evaluate coronary artery disease (CAD) and also an effective prognostic tool for patients with CAD. However, few studies investigated the prognostic value of attenuation correction (AC) in MPI, and the results were controversial. Objectives To investigate the prognostic value of computed tomography (CT)-based AC thallium-201 (Tl-201) MPI. Methods A total of 108 consecutive patients who underwent Tl-201 MPI and received coronary angiography within 90 days were included. Medical records were reviewed and missing information was completed after telephone contact. The prognostic value was evaluated by Kaplan-Meier analysis, univariable and multivariable Cox proportional hazards model. Results After a mean follow-up of 7.72 ± 3.72 years, 27 patients had died, 41 had been readmitted for cardiovascular (CV)-related events and 44 had reached the composite of death plus CV-related re-admission. Kaplan-Meier curves for all-cause mortality for SSS with a cutoff value of 13 for AC and 16 for non-AC (NAC) images showed a significant difference between the two curves for both AC and NAC images (p = 0.011 for AC and p = 0.021 for NAC). In the multivariable model, SSS and SRS showed similar independent predictive values in predicting all-cause mortality and composite of all-cause mortality plus CV-related re-admission, in both AC and NAC images. Subgroup analysis implicated that AC MPI possibly provided better risk stratification in obese patients. Conclusion CT-based AC and NAC MPI showed similar value and were the only significant predictors for the composite of mortality and CV events.